Role of seed in transforming of agriculture in Myanmar - Oo, Tin Htut; Shwe, Tin Maung (International Food Policy Research Institute, 2014)
Agriculture, including fisheries and forestry, accounted for 36.4 percent of Myanmar’s GDP in 2010-2011. Approximately 69 percent of the total population of 59.78 million (2010-2011) lives in rural areas and 61.2 percent of the total labor force is employed by the agricul-ture sector (MOAI 2012). The government has designated the agriculture sector as a main pillar of the economy and is dedicating vari-ous efforts and investments to achieve greater progress in the sector. Rice is the primary crop, followed by maize, pulses, and oil seeds. Over 90 percent of the total rice sown in Myanmar1 is done so by farmers’ reusing their seeds. Hybrid varieties of maize are grown more widely in part due to domestic hybrid production and imports. In recent years, there has also been an increase in the production of fruits and vegetables due to demand from China as well as the emergence of supermarkets in the country which has also increased the utilization of quality seeds and seedlings.